EXCHANGE RATE AND INFLATION INTERACTIONS AND THEIR IMPACT ON HAJJ COSTS: A VECM APPROACH - Dewi Fazira; Khairina Tambunan; Nuri Aslami (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2026)
This study aims to analyze the effects of exchange rates and inflation on the cost of the Hajj in Indonesia during the period 1996–2025. The data used consists of annual time-series secondary data sourced from the Central Statistics Agency (BPS), Bank Indonesia, and the Ministry of Religious Affairs of the Republic of Indonesia. The analysis method used is the Vector Error Correction Model (VECM). The results of the Johansen cointegration test indicate a stable long-term relationship between the variables. The research findings through VECM estimation show that in the long run, the Exchange Rate (t-stat 2.51) and Inflation (t-stat 7.03) have a positive and significant effect on Hajj Costs. The results of the Variance Decomposition for the 10th period show that the Exchange Rate contributes a larger shock of 4.86% compared to Inflation at 2.82% to the variation in Hajj Costs. This indicates that the stability of the Rupiah exchange rate is a crucial factor in determining Hajj costs in Indonesia